Scanning by DOVAM-S Detects All Unique Sequence Changes in Blinded Analyses: Evidence that the Scanning Conditions Are Generic - C.H. Buzin; C.Y. Wen; V.Q. Nguyen; G. Nozari; A. Mengos; X. Li; J.S. Chen; Q. Liu; R.A. Gatti; F.K. Fujimura; S.S. Sommer (BioTechniques)
The [detection of virtually all mutations]-SSCP (DOVAM-S) is a highly sensitive variant of single strand conformation polymorphism (SSCP). Mutations in the factor IX gene were used to find a set of five SSCP conditions that detects virtually all mutations. A blinded analysis of the factor IX gene in patients with hemophilia B detected 82 of 82 unique mutations. Since the method was developed and tested on the factor IX gene, it is possible that the conditions selected work more efficiently in the factor IX gene than in other genes. To test the general applicability of the conditions under which DOVAM-S detected all mutations in this gene, blinded analyses were performed in the human factor VIII and ataxia-telangiectasia (ATM) genes. Segments were amplified individually, combined into groups of 16 to 18 amplified segments and electrophoresed in five different nondenaturing conditions of varying matrices, buffers, temperatures and additives. Blinded analyses were performed in 92 samples from patients with hemophilia A (factor VIII gene) and 19 samples from A-T patients (ATM gene). Combined with an earlier blinded analysis in the factor IX gene, all of the 250 mutations and polymorphisms (180 of which are unique) were detected in both analyses. For two, three and four joint conditions, the average detection frequency ranged from 77%–97%, 91%–100% and 95%–100%, respectively. For each of the genes, one mutation may have been missed if only four conditions were used. With DOVAM-S, approximately 500 kb of autosomal sequence can be scanned in five gels with virtually 100% detection of mutations within the scanned region. The detection of 180 out of 180 unique sequence changes implies that DOVAM-S detects at least 96.5% (P=0.03) of mutations. Blinded analyses that detect 400 unique sequence changes are required to determine that a scanning method detects at least 98.5% of mutations.